Structural characterization and bioactivity evaluation of water-extractable polysaccharides from chickpeas (Cicer arietinum L.) seeds - Zhu, Yingying; Dun, Baoqing; Shi, Zhenxing; Wang, Yuanji; Wu, Li; Yao, Yang (Frontiers in Nutrition, 2022)
Two water-extractable polysaccharide fractions designated as CWP (7.37×105 Da) and CWP-0.2 (1.58×104 Da) were isolated and purified from chickpea (Cicer arietinum L.) seeds. The chemical structure of the two polysaccharides was characterized by various methods. Monosaccharide composition and methylation analysis showed that CWP was composed of Man and Glc in a molar ratio of 44.6:55.4, and CWP-0.2 was composed of Rha, Ara, Man, Glc, and Gal in a molar ratio of 10.6:23.3:5.2:4.9:56. Further structural characterization indicated that the main chain connection of CWP was →(2-β-d-Fruf-1) n→, and the main chain connection of CWP-0.2 was explored as →2,4)-α-l-Rhap-(1→3)-α-d-Galp-(1→ with the branched chain of →2,4)-α-l-Rhap-(1→o-4. Besides, both CWP and CWP-0.2 had antioxidant and immunoregulatory activity in vitro, through scavenging DPPH· and ABTS·+ as well as stimulating production of NO, IL-6, TNF-α and MCP-1 in RAW 264.7 macrophages. CWP-0.2 revealed significantly higher bioactivity than CWP.